2006
DOI: 10.1007/s10346-006-0036-1
|View full text |Cite
|
Sign up to set email alerts
|

Global landslide and avalanche hotspots

Abstract: Allocating resources for natural hazard risk management has high priority in development banks and international agencies working in developing countries. Global hazard and risk maps for Rank landslides and avalanches were developed to identify the most ex- posed countries. Based on the global datasets of climate, lithology, earthquake activity, and topography, areas with the highest hazard, or “hotspots”, were identified. The applied model was based on classed values of all input data. The model output is a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
281
2
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 501 publications
(292 citation statements)
references
References 3 publications
5
281
2
4
Order By: Relevance
“…Italy is one of the European countries with the highest percentage of landslide prone landscape (13%, according to Nadim et al 2006). The slope movements are responsible for a considerable annual economic loss for the Nation, estimated 0.3-0.4% of the gross domestic product (Canuti et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Italy is one of the European countries with the highest percentage of landslide prone landscape (13%, according to Nadim et al 2006). The slope movements are responsible for a considerable annual economic loss for the Nation, estimated 0.3-0.4% of the gross domestic product (Canuti et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Earthquakes, floods, and landslides are among the major threats to urban areas [1,2]. During the 1990s, nearly nine percent of the world's natural disasters were landslides, which are difficult to predict [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to other natural hazards (e.g., floods or earthquakes), which affect large areas, landslides are generally limited in area but can occur with a high frequency in a specific region (JRC 2011). Landslides can be caused by both natural and anthropogenic actions, and landslide disasters are increasing worldwide (Andersson-Sköld et al 2014;Guzzetti 2016;Ho et al 2013;Nadim et al 2006;SOU 2007). The reasons are suspected to be increased susceptibility of surface soil to instability because of deforestation and overexploration of natural resources, greater vulnerability of exposed population as a result of urbanization and uncontrolled land use, and climate change resulting in a greater potential for weather extremes (Lacasse et al 2010;Nadim et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Landslides can be caused by both natural and anthropogenic actions, and landslide disasters are increasing worldwide (Andersson-Sköld et al 2014;Guzzetti 2016;Ho et al 2013;Nadim et al 2006;SOU 2007). The reasons are suspected to be increased susceptibility of surface soil to instability because of deforestation and overexploration of natural resources, greater vulnerability of exposed population as a result of urbanization and uncontrolled land use, and climate change resulting in a greater potential for weather extremes (Lacasse et al 2010;Nadim et al 2006). Pereira et al (2014) have found that most landslides occur during the wettest months, reflecting the importance of rainfall-triggering mechanisms.…”
Section: Introductionmentioning
confidence: 99%